Salafism and politics: a Malaysian case - Malik, Maszlee (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2016)
Amongst the unanticipated phenomenon of the Arab Spring is the emergence of the “political Salafis” through the active participation of the Salafi groups in the politics of some countries affected by the uprisings. However, in Malaysia, a group of Salafism preachers has preceded their brethren in Egypt. Malaysian salafis joined the ruling nationalist party, UMNO (United Malays National Organisation), in 2009. They justify their participation in UMNO by arguing that they are following the Salafi doctrine of “total obedience to the rulers” (Ta’at Wulat al-Umur), “the prohibition of rebelling against the rulers” (Tahrim al-Khuruj ‘ala al-Hukkam) and the doctrine of “necessity renders prohibited things permissible” (al-Darurat tubihu al-mahzurat). Though their participation in politics is due to political expediency, it has been beneficial for both the Salafis and the regime. This paper, applying the historical and descriptive method, examines those Salafists’ theological arguments and motivations.